Cardiovascular risk factors of Alzheimer's disease and other neurocognitive disorders in Malaysia - Ibrahim, Buhari; Suppiah, Subapriya; Piersson, Albert Dayon; Razali, Rizah Mazzuin; Mohamad, Mazlyfarina; Abu Hassan, Hasyma; Ibrahim, Normala (Lippincott, Williams & Wilkins, 2021)
Introduction: Risk factors for cardiovascular disease (CVD) have been increasingly implicated in the development of dementia but little is known about the effects in a Malaysian population. We aimed to determine the interaction between sociodemographic and CVD risk factors among the dementia and mild cognitive impairment (MCI) patients in Malaysia. Materials and methods: A cross-sectional study was conducted in the memory clinic at Hospital Kuala Lumpur (HKL). Medical records data from 2014 to 2019 were extracted. Mini Mental State Examination (MMSE) test was used to assess the neurocognitive function of patients. Results: A total of 298 patients (30 MCI, and 268 dementia) were evaluated, with dementia patients consisting of 78 Alzheimer's disease (AD), 93 Vascular dementia (VaD), 94 Mixed dementia, 2 early-onset Alzheimer's disease (EOAD) and 1 Logopenic Progressive Aphasia type of AD (LPA). MCI and dementia were significantly associated with a history of CVD, particularly stroke (p=0.023). Conclusion: Given that stroke significantly predicted the risk of developing vascular dementia among the patients in a central Malaysian population, lifestyle modifications are recommended to alleviate these risk factors of CVD.